MERANCANG HOTEL BINTANG 5 DI PALANGKA RAYA DENGAN PENDEKATAN DESAIN GREEN ARSITEKTUR - Saragih, Merry Noviyanti; Hamidah, Noor (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2024)
Its increasingly rapid development, Palangka Raya City is also developing rapidly through more advanced and competitive infrastructure. Hotels are a supporter of the economy and tourism in increasing economic and tourism growth in the City of Palangka Raya. Hotels are lodging facilities that provide accommodation, food and additional services to guests visiting Palangka Raya City. The aim of designing the hotel is to utilize building technology that applies the concept of green architecture. Design methods using qualitative methods are explored from comparative study analysis and precedent analysis. The comparative study uses a hotel function approach based on observing building objects with the same function to determine the type of hotel, types of rooms offered, circulation arrangements, utility networks and hotel facilities. Analysis of precedent studies using a green architecture approach through site analysis, circulation, analysis of renewable energy needs, shape and building appearance. The results of the Green Architecture plan in this Hotel building are implemented by utilizing reprocessed rainwater for user needs and watering plants, utilizing sunlight for natural lighting and storing thermal energy using solar panels to save energy, providing natural ventilation to obtain optimal space ventilation, also the application of a roof garden as a garden and to shade the space of a multi-story building. Green architecture applied in buildings is able to save energy and costs and does not damage the surrounding environment